Pengaruh Motivasi , Kepuasan Kerja, Dan Lingkungan Kerja Terhadap Kinerja Pegawai Negeri Sipil Di Kantor Dinas Sosial Kabupaten Malang - Astri Sukma Andini; Abdul Kodir Djaelani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determinane the influence of Motivation, Job Statisfaction and Work Environment on the performance of civil servants at the Social Service of Malang Regency. The sampling technique used saturated samples obtained from 43 employees. The data collection method used a questionnaire technique that is distributed directly to employees of the Malang Regency Sosial Service. The data analysis technique used in this study is multiple linear regression. The result showed that motivation affects employee performance, job statisfaction affects employee performance and the work environment also affects employee performance Keywords: Motivation, job Satisfaction,Work Environment, Performance